Perspektif Masyarakat Sulawesi Tengah terhadap Isu dan Dampak Perubahan Iklim - Alfiandy, Solih; Hamid, Syarwan; Ilahi, Asep Firman; Sunardi, Sunardi (Buletin GAW Bariri (BGB), 2025)
Limited public understanding and perception of climate change indicate that adaptive capacity at the local level remains constrained. This study aims to examine the perceptions, awareness, and engagement of Central Sulawesi communities regarding climate change. A mixed-mode survey—offline and online—was conducted using a questionnaire with 14 structured items and an open-ended essay prompt for additional suggestions. From the sampled respondents drawn from the entire population of Central Sulawesi, the Margin of Error (MoE) was calculated at 7.92%, with a confidence level of 92.08%. The findings reveal that 96% of participants are aware of climate change, although only a small proportion consider themselves well-informed. Furthermore, 75% regard climate change education as highly important, and 96% identify social media as an effective means for disseminating climate knowledge. Moreover, 43% of respondents believe climate change significantly affects their lives, and 45% express concern about its impacts. A majority support mitigation efforts, endorsing reforestation and educational programs as priority strategies. While public awareness appears relatively high, a gap persists between knowledge and tangible action. These insights highlight community readiness—and existing limitations—for supporting local-level climate change interventions.